Awareness of Food Safety among 1874 Secondary Students in Tripoli city, Libya - Abuhlega, Thuraya Ahmed (Jordan Journal of Agricultural Sciences, 2020)
What distinguishes secondary students is that they are in adolescence and this age group is known for its tendency for non-compliance and out of the ordinary. Thus, they are more prone to foodborne diseases. This study aimed to assess food safety knowledge and practices among secondary students at twelve public secondary schools in all six municipalities in Tripoli city, Libya. A cross-sectional survey was carried out among 1874 students in which 55.2% of the respondents were females and 44.8% were males. The majority of the respondents (71.5%) were between the age of 16 and 17 years. Data were analyzed by the SPSS. The findings revealed that 83.4% and 87.5% of students have good knowledge and a moderate level of practices of food safety, respectively. The findings also revealed that only 7.8 % of students reported that they "always" wash their hands before eating breakfast in school. It was observed that there was a significant association between food safety knowledge scores and students’ municipality and a significant association between food safety practices scores and students’ municipality, and mothers’ education level of secondary school students (P <0.05). In conclusion, there was a weakness of some important knowledge points and practices of food safety. Therefore, an effective and continuous education program for these teenagers is necessary. Also, the authorities should provide appropriate facilities at schools that enable students to wash their hands.